Numerical Simulation of Groundwater Flow and Pollution Transport Using the Dual Reciprocity and RBF Method - Kovarik, Karel (Communications - Scientific letters of the University of Zilina, 2010)
Transport of pollution is strongly influenced by groundwater flow. All numerical models of transport equation must be based on the groundwater flow models. The most of them suffer from numerical diffusion and/or oscillations of solution. Both phenomena lower the quality of results of these models. Plenty of authors are working on improving the quality of the numerical simulation. This paper presents the connection between a dual reciprocity method used to model groundwater flow and the meshless radial basis function methods used for a transport model. Both methods are one of the latest tools for modeling these phenomena.